Penguatan 5 Pilar dalam Upaya Penurunan Stunting di Kelurahan Simokerto Kota Surabaya - Triannisa Wahyu Agitiya; Tiara Tivany (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to find out the five pillars in efforts to reduce stunting in Simokerto Village, Surabaya City. Research data collection using Focus Group Discussion (FGD). The targets of the EMAS Stunting Village Thematic KKN are brides-to-be, pregnant women, postpartum mothers and Baduta and toddlers. The results showed that there were 5 pillars of cultivation carried out by each "Golden Village" group in each village. Pillar 1 in the form of increasing village government commitment and leadership has activities in the form of collecting village commitments related to accelerating stunting reduction through the FGD forum. Pillar 2 related to strengthening and developing systems, data, information, and research has activities to collect and analyze demographic data related to stunting, assistance in stunting surveillance and growth and development, assistance in Rumah DataKu, and assistance in auditing stunting cases. Pillar 3 discusses communication of behavior change and community empowerment in terms of nutrition, healthy behavior, mutual assistance, and independence which has activities including training and education based on nutrition and health behavior change, development of nutrition and health education media. Pillar 4 is on the convergence of specific and sensitive interventions through a quality family village approach with programs implemented in the form of situation analysis related to hygiene and sanitation as well as the availability of clean water, development and development of healthy environments, and clean water surveys. Pillar 5 discusses food security at the individual, family, and community levels through optimizing the use of local food ingredients with activities in the form of local food potential map analysis, food consumption surveys, and market surveys. The implementation of the five pillars is carried out in Simokerto Village well and is adjusted to the needs of the relevant village.